Academic Writing: A Handbook for International Students (3rd Ed.) - Bista, Krishna; Shultz, Pamela (Journal of International Students, 2011)
For many international students, academic writing is a significant challenge because of the rules used in Standard English. Writing in academia consists of producing college essays, reflections, reports, and research papers which all require a working knowledge of the English language. Nevertheless, English Composition instructors, English as a Second Language (ESL) program staff, and freshmen international students will find Bailey’s book Academic Writing text a helpful resource manual both in and out of class.